Hidrólise do óleo da amêndoa da macaúba com lipase extracelular de "Colletotrichum gloesporioides" produzida por fermentação em substrato líquido - Luciana Amaral de Faria (2010)
Extracellular lipase production by the filamentous fungi Colletotrichum gloesporioides was tested using two fermentation methods: in liquid substrate and in solid substrate. The liquid substrate fermentation yielded a larger production of lipase by this microorganism andwas selected as the method for obtaining the extracellular lipase crude solution. Aliquots of the lipase crude solution stored at 4° C and at - 20° C were not stable, and presented a progressive decrease in lipase activity. The crude solution was then concentrated by ultrafiltration, reaching a recovery of 81% of the lipase activity and a 1.5 fold concentration factor. Then, the concentrated lipase solution was lyophilized. This process led to stabilization, through time of the lipase activity of the lyophilized solution, which was applied on the preliminary tests of the enzymatic hydrolysis of olive oil. These tests led to the adjusted equation which explained the variation of hydrolysis degree in relation to the simultaneous variation of enzyme concentration and reaction time: y = 35,25 + 3,19x1 + 8,65x2. The hydrolysis degree of the olive oil varied between 18.8 and 43.7%, and there was a 57% increase in the reaction yield. Finally, the evolution of the Macaúba kernel oil was followed up, based on the combination which was chosen as the most advantageous, from the olive oil hydrolysis, reaching a direct relationship between the degree of hydrolysis and the reaction time.